Novel conjunctive groundwater-surface water management for controlling floods and droughts [Abstract only] - Brindha, Karthikeyan; Pavelic, Paul; Lagudu, Surinaidu; Muthuwatta, Lal P.; Eriyagama, Nishadi; Amarnath, Giriraj; Smakhtin, Vladimir U. (2014)
Well-targeted programs of conjunctive use of groundwater and surface water can help overcome the problem of both floods and droughts, or in other terms meet the water demands for domestic as well as irrigation needs during the dry season. Addressing this, a novel form of conjunctive use management has been developed that involves strategically recharging floodwater in upstream areas to boost small-scale groundwater irrigation and to protect floodaffected areas downstream. For this, choice of site is a crucial component to implement the approach. A method was devised using GIS tools using readily available data from secondary sources to arrive at a suitability index to rank prospects across the entire Ganges basin. This basin was chosen because it has a well-known history of devastating flooding events and water shortage in dry months and is one of the largest and most heavily populated river basins in the world. Numerical modelling is being applied to an area characterized as having high prospects to help to understand the interactions between the groundwater and surface water and the impact of floods on groundwater system. One of the main components to be identified from the model is the peak flows to be captured successfully for recharge. This utilisation of high flows by diverting from the rivers to storage structures introduced within the model will help to identify the potential to manage and reduce the flood impact. This model can help to decide on the size and placement of the structures to store water for maximum recharge and subsequently in watershed management. The relationship between floodwater storage and recharge, and the optimisation of these two processes can also be brought out. Opportunities for conjunctive use of water identified by mapping and the understanding gained from modelling is to be piloted out in one of these sites to establish technical and institutional feasibility with the view to promoting larger-scale implementation.